Monday
March 27, 2017

Post a New Question

Posted by on .

if (a+b)squared=64, and ab=3, find a squared+ b squared

  • Math - ,

    we can also rewrite this (a+b)squared=64 as
    (a+b)^2 = 64
    first we expand (a+b)^2
    (a+b)^2 = 64
    (a+b)(a+b) = 64
    a^2 + 2ab + b^2 = 64
    since we are given the value of ab, which is ab = 3, we can substitute it here:
    a^2 + 2(3) + b^2 = 64
    a^2 + 6 + b^2 = 64
    a^2 + b^2 = 64 - 6
    a^2 + b^2 = 58

    hope this helps~ :)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question